Electrochemical Corrosion Behaviors of 6082 Aluminum Alloy in Different Supply Status - HAN Chao (Cailiao Baohu)
For understanding the electrochemical behaviors of 6082 aluminum alloy in simulated snowmelt agent environment, the corrosion resistant performance of 6082 aluminum alloy under different supply status was studied by electrochemical impedance spectroscopy and dynamic potential polarization curves in different mass fraction (0.8% and 1.5%) NaCl solutions. After the electrochemical corrosion, the microstructural morphology analysis of the samples was conducted by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. Results showed that the Nyquist curves in the electrochemical impedance spectroscopy of 6082 aluminum alloy were composed of two capacitive reactance arcs, and two characteristic peaks appeared in the frequency-phase angle Bode diagram. The concentration of solution and the supply status of alumium alloy had a great influence on the corrosion current density in the dual polarization curve. With a certain NaCl solution concentration, the corrosion resistance of 6082 aluminum alloy in T6 state was better than T1 state. Under a certain supply state, the corrosion resistance of 6082 aluminum alloy decreased with the increase of NaCl solution concentration. Meanwhile, the electrochemical corrosion of 6082 aluminum alloy was characterized by extensive intergranular corrosion caused by local pitting.